Factors affecting population density and colonization success of two non-native beetle species with different breeding/life-history strategies - Cocoș, Dragoș; Klapwijk, Maartje J.; Björkman, Christer; Ravn, Hans Peter; Schroeder, Martin (Frontiers in Forests and Global Change, 2024)
IntroductionBark and longhorn beetles have become of increasing concern as invasive pests as they are transported across the globe. The larch bark beetle Ips cembrae and the larch longhorn beetle Tetropium gabrieli are two species that have recently established in Scandinavia. We asked the following questions for both I. cembrae and T. gabrieli: (i) How does habitat availability affect the relative population density? (ii) How is the colonization probability related to the relative population density? (iii) What is the relationship between relative population densities of the beetles and enemy pressure?MethodsThe relative population density of the two beetle species were assessed with two pheromone-baited traps for each beetle species in 36 pure larch stands distributed in southern Sweden and Denmark. In addition, colonization success was recorded on five cut larch trees in 30 of the 36 larch stands.ResultsIps cembrae was trapped in 19 stands and had colonized cut trees in two stands, whereas Tetropium gabrieli was trapped in 18 stands and had colonized cut trees in 12 stands. Both species showed a positive relationship between the relative population density and the probability of colonization of the cut trees. For I. cembrae a higher population size was required for colonization than for T. gabrieli. The relative population density of both species was positively related to the amount of habitat.DiscussionThe difference in the population size required for colonization between the two studied species might be explained by their different reproductive strategies. The results are discussed in terms of host location and mate finding, and predation pressure.